Merkel cell carcinoma in renal transplant recipients: case reports and literature review - Jaśkiewicz, Dorota; Imko-Walczuk, Beata; Jaśkiewicz, Janusz; Lizakowski, Sławomir; Dębska-Ślizień, Alicja; Rutkowski, Bolesław (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Merkel cell carcinoma (MCC) is a rare, but very aggressive tumour of neuroendocrine cell origin. Long-term immunosuppression is proven to play one of the most significant roles in MCC development. Organ transplant recipients represent an important percentage of patients with Merkel cell cancer. Prognosis in this group is poor, apparently worse than in non-immunosuppressed patients with MCC. Objective . To present differences in Merkel cell carcinoma between patients undergoing immunosuppressive therapy and the general population. Case reports. Case 1. A 69-year-old male patient, who underwent kidney transplantation, was referred to the Dermatology Department, because of a facial skin tumour. The lesion was surgically removed and Merkel cell carcinoma diagnosis was confirmed histopathologically. The doses of immunosuppressants were decreased and the patient is under dermatological care with no further progression. Case 2. A 72-year-old female kidney transplant recipient visited a dermatologist, due to a lesion on her forehead. Histopathology test revealed Merkel cell carcinoma. Computed tomography showed metastases in regional lymph nodes and lungs. The patient died six months after occurrence of the skin lesion. Case 3. A 79-year-old male patient after kidney transplantation was examined in the Dermatology Department, presenting a tumour on his right nostril. Initially a squamous cell carcinoma was diagnosed and he underwent radiotherapy. After 18 months, he was readmitted to the hospital, due to a significant lymph node enlargement. Histopathological examination revealed Merkel cell carcinoma. The patient died because of lung metastases. Conclusions . Merkel cell carcinoma presents a much higher incidence and worse prognosis in organ transplant recipients than in the general population. Therefore to reduce the significant potential of morbidity and mortality, the search for better methods of prevention is necessary.